Quantitative Comparison of Proteomes Using SILAC. (20th September 2018) - Deng, Jingjing; Erdjument‐Bromage, Hediye; Neubert, Thomas A.
Abstract: Stable isotope labeling by amino acids in cell culture (SILAC) has become very popular as a quantitative proteomic method since it was firstly introduced by Matthias Mann's group in 2002. It is a metabolic labeling strategy in which isotope‐labeled amino acids are metabolically incorporated in vivo into proteins during translation. After natural (light) or heavy amino acid incorporation, differentially labeled samples are mixed immediately after cell lysis and before any further processing, which minimizes quantitative errors caused by handling different samples in parallel. In this unit, we describe protocols for basic duplex SILAC, triplex SILAC for use in nondividing cells such as neurons, and for measuring amounts of newly synthesized proteins. © 2018 by John Wiley & Sons, Inc.